The Role of Concurrent Chemo Radiation in Locally Advanced Esophagel Cancer - Muhammad Sibtain Shah, Jeanado Khan, Abdul Manan Soornro Muhammad Sibtain Shah, Jeanado Khan, Abdul Manan Soornro (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2018)
Objective: To assess the response of cisplatin & 5 flurouracil based concurrent cherno radiation in locally advanced esophageal cancer. Methods: This descriptive case series study was conducted in the Department of Clinical Oncology LINAR Cancer Hospital Larkana from Januay 2016 to August 2017 ,on histological proven squamous cell carcinoma of esophagus fulfilling inclusion criteria. Excluding cases with carcinoma of cervical esophagus, infiltration of tumor in tracheobronch i al tree, distant metastasis. We planned our patients with EBRT have total dose of radiation 50.4Gy in 28 fractions. Inj Cisplatin 75mg/m2 IV DI & Inj 5- Flurouracil 1000mg/m2 IV D l to D4 were infused during & 5th week of external beam radiotherapy & 8th & 11 th weeks. The response of treatment was assessed four weeks later radiologically on CT scan chest & abdomen with contrast. The data was statistically analyzed. Results: Majority of patients having age above 40 years. The average age of patients & duration of disease were 46.45- -10.59 years (95%0: 46.45+1- 10.59) and 3.5 +/-1.17 months (95%0:3.20 to 3.80) respectively. 27(43.5%) were male & 35(56.5%) were female. The response of treatment was assessed four weeks later radiologically on CT scan chest & abdomen with contrast according to response evaluation criteria in solid tumors (RECIST). Complete response rate was 24.2% and partial response rate was 50%.Progressive disease was observed in 6.5% cases and disease was stable in 19.4% cases. Conclusion: Con-current pre-operative Chemo-radiation for locally advanced esophageal cancer is associated with good clinical response and it is very effective and safe in our setting.